Germanium diode and transistor - Borromeo, Ernesto S. 1936- ([Quezon City s.n.], 1968)
The study presented a method of teaching germanium diode and triode transistor to secondary school students with the aid of demonstrations and guided by the PSSC approach.
Thesis (M.A.T. Physics)--University of the Philippines
Keywords: Germanium diodes; Transistors